Принципы построения сетевых систем обнаружения вторжений на базе ПЛИС - Коростиль, Ю.М.; Гильгурт, С.Я. (Моделювання та інформаційні технології, 2010)
The common principles of FPGA-based NIDS (Network Intrusion Detection Systems) construction are investigated. The main requirements and characteristics of such systems are discussed. The generalized structure of a reconfigurable NIDS is described.